2017
DOI: 10.1001/journalofethics.2017.19.2.ecas2-1702
|View full text |Cite
|
Sign up to set email alerts
|

How Should Therapeutic Decisions about Expensive Drugs Be Made in Imperfect Environments?

Abstract: Clinicians must inevitably make therapeutic decisions under nonideal conditions. They practice in circumstances that involve incomplete evidence. They deliver care in health care systems that are complex and poorly coordinated. Each of the patients that they take care of is unique while research offers evidence regarding relatively homogeneous populations of patients. Under these circumstances, many partiesmedical scientists, reviewing agencies, insurers, and accountable care organizations-can and should contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Nonetheless, as Fleck and Danis argue, within their own hospitals, clinicians can make a big difference in the inclusion (or exclusion) of cancer drugs as part of their accountable care organizations’ bundled treatment plans. 69 Indeed, Hunter et al, in their retrospective analysis of dialogues from 1755 outpatient visits in community-based practices nationwide from 2010 to 2014 (which involved 677 patients who had breast cancer), noted that one of the strategies to reduce OOP costs involved switching from oral therapies with high copays (eg, ibandronic acid, alendronate sodium) to intravenous infusion therapies (eg, zoledronic acid), which were described as having little or no copays. 70…”
Section: The Role Of Clinicians In Managing Financial Toxicitymentioning
confidence: 99%
“…Nonetheless, as Fleck and Danis argue, within their own hospitals, clinicians can make a big difference in the inclusion (or exclusion) of cancer drugs as part of their accountable care organizations’ bundled treatment plans. 69 Indeed, Hunter et al, in their retrospective analysis of dialogues from 1755 outpatient visits in community-based practices nationwide from 2010 to 2014 (which involved 677 patients who had breast cancer), noted that one of the strategies to reduce OOP costs involved switching from oral therapies with high copays (eg, ibandronic acid, alendronate sodium) to intravenous infusion therapies (eg, zoledronic acid), which were described as having little or no copays. 70…”
Section: The Role Of Clinicians In Managing Financial Toxicitymentioning
confidence: 99%
“…[25][26][27][28] Providers can also play a significant role in the inclusion (or exclusion) of cancer drugs as part of their accountable care organizations' bundled treatment. 29 Lastly, our results illuminate areas in which health care systems can partner with communities to respond to social risks such as low health literacy, social isolation, and cultural misconceptions. Low health literacy is an under-appreciated factor in cancer control communication and patient decision-making.…”
Section: Cancer Prevention and Control Determinants -Jou Et Almentioning
confidence: 68%
“…These exemptions are particularly needed when the disease highly interferes with patients’ daily life. Previous studies have shown that therapeutic decisions should indeed be patient centered, fair, and cost-effective in the ideal situation [ 41 ]. However, this remains a practical challenge, partly because of the lack of insight into cost-effectiveness of the recently introduced therapies in daily practice [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A shift toward more patient-centered indication criteria incorporating the disease impact in daily life in addition to current criteria concerning therapeutic history would be highly appreciated by patients. This would facilitate in making “fair” choices, in particular for expensive therapies [ 8 , 41 ]. Agencies such as the FDA and the NHS also promote patient-centered care, with improved patient access to more affordable drugs [ 43 – 45 ].…”
Section: Discussionmentioning
confidence: 99%